Remmal Khoja. Chronicle “Tarih-i Sahib Giray Khan” (“History of Khan Sahib Giray”). Part 3. - Refat Abduzhemilev (Крымское историческое обозрение)
To the attention of the readers is offered the Russian translation of the fragments from the chronicle «Tarikh-i Sahib Geray Khan» (XVI c.) The beginning of the work was published in the previous issue of the journal. The chronicle’s author was a prominent scholar, a court astrologer at the court of Sahib Geray Khan, Kaysuni-zade Mehmed Nidai, well known under the penname Remmal Khoja. Along with the factual component of the chronicle, the artistic specifics are also important. In comparison with the other works of historiography orientation, this work most clearly demonstrates the power of an artistic word, its aesthetic potential. The work is written in panegyric form, the author praises the heroic deeds being done during the Khanate of Sahib Geray. In the chronicle are revealed the traditions of Ottoman historiography. The translation was made from the Turkish edition of «Tarih-i Sahib Geray Han (“Histoire de Sahib Giray, Khan de Crimee de 1532 a 1551”, Ankara, 1973) ». The author of the translation tries to correlate the content of the translation with the content of the original, to convey the artistic embodiment of historical events, to preserve the style of the work, to preserve the realities of the language of the Khan’s era if possible. The text will be useful for specialist in the history and literature of the Crimean Khanate.